2006
DOI: 10.1002/dvdy.20822
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Hoxa5 function controls the growth and differentiation of mammary alveolar epithelium

Abstract: Recent progress has enlightened the involvement of Hox genes in organogenesis. Several Hox genes are expressed in normal and neoplastic mammary glands. Using Hoxa5 mutant mice, we showed that Hoxa5 Ϫ/Ϫ females present nursing defects. Characterization of the Hoxa5 Ϫ/Ϫ mammary gland phenotype reveals changes in proliferation and differentiation of the epithelium of nulliparous and pregnant Hoxa5 Ϫ/Ϫ females that precede the abnormal secretory activity at parturition. These defects likely underlie the incapacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…PG9 genes, for example, are implicated in mammary gland maturation, expansion and differentiation (Chen and Capecchi, 1999). The control of cell differentiation has also been well documented for Hoxa5 in the mouse, which instructs epithelia from stromal cells in the lungs, gut and mammary gland (Aubin et al, 2002;Boucherat et al, 2012;Garin et al, 2006). In vertebrates, several Hox genes have been shown to either promote or inhibit vascular development or remodelling (Stoll and Kroll, 2012), supporting a general view that Hox proteins directly modulate effector genes involved in the control of cell-cell and cell-extracellular matrix interactions (Kachgal et al, 2012;Winnik et al, 2009).…”
Section: An Overview Of the Hox Gene Familymentioning
confidence: 98%
“…PG9 genes, for example, are implicated in mammary gland maturation, expansion and differentiation (Chen and Capecchi, 1999). The control of cell differentiation has also been well documented for Hoxa5 in the mouse, which instructs epithelia from stromal cells in the lungs, gut and mammary gland (Aubin et al, 2002;Boucherat et al, 2012;Garin et al, 2006). In vertebrates, several Hox genes have been shown to either promote or inhibit vascular development or remodelling (Stoll and Kroll, 2012), supporting a general view that Hox proteins directly modulate effector genes involved in the control of cell-cell and cell-extracellular matrix interactions (Kachgal et al, 2012;Winnik et al, 2009).…”
Section: An Overview Of the Hox Gene Familymentioning
confidence: 98%
“…Hoxb5 and Hoxc5 mutant mice are viable and no organ defect has been described (8,43). In contrast, the loss of Hoxa5 function results in a panoply of phenotypes indicative of the broad range of Hoxa5 actions throughout life, including tracheal and lung dysmorphogenesis responsible for the high neonatal mortality rate of Hoxa5 Ϫ/Ϫ pups (1,2,4,17,19,29,36). Surviving Hoxa5 Ϫ/Ϫ mice display an emphysema-like phenotype characterized by air space enlargement and goblet cell metaplasia (33).…”
mentioning
confidence: 93%
“…In the studies done by Boucherat et al and Garin et al, the immunostaining pattern of HOXA5 was located in the pulmonary epithelium nuclei during the pulmonary development 12,34. However, another study found different expression pattern in the pulmonary malignancy.…”
Section: Discussionmentioning
confidence: 92%